The Influence of Kinesics and Vocalic in ESL Oral Presentation among Undergraduates - Rahmat, Noor Hanim; Roslan, Muhammad Aizuddin; Othman, Noor Ahnis; Ramli, Nor Fazlin Mohd (Global Journal of Social Sciences Studies, 2019)
Oral presentations have become part of many course assessments. During presentations, presenters use verbal and non-verbal cues. Learners Nonverbal cues are used either directly or indirectly by presenters to express their feelings towards the oral presentation. Some common nonverbal cues often used are kinesics and vocalic. Kinesics is derived from the word ‘kinesics’ which means ‘movement’ and refer to the hands, legs, body and facial movements. Vocalic is the study of voice and it is used to address a message for example like the tone of voice This study is done to explore the influence of kinesics and vocalic in ESL orang presentation among ESL learners. 30 undergraduates responded to a questionnaire about how they perceive the use of kinesics and vocalics in oral presentations. Findings revealed ESL learners used a variety of nonverbal cues in their presentation for different reasons in their presentations. The results of this study bear interesting pedagogical implications for classroom teaching and learning of ESL oral presentations.